DECISION-MAKING SYSTEM BASED ON VOICE-EMOTIONAL COMANDS FOR EMERGENCY INTERVENTION - ABABII, VICTOR; SUDACEVSCHI, VIORICA; BOROZAN, OLESEA; FRATAVCHAN, VALERIY (Чернівці: Черн. нац. ун-т, 2022)
Development of new technologies, which are oriented to audio signal processing, has also launched new directions in the use thereof in various spheres of science and engineering. A very important sphere may be considered the Human-Robot interaction aimed to generate orders-fulfilment or to realize a question-answer dialog. Human voice is regarded as unique characteristics, which may serve as personal or emotional identification of human being. Hence, such characteristics are used in this thesis to generate the decision, which is based on voice and emotional orders, aiming to interfere in emergency cases, in the course of the technological process of complex robotized systems operation.
Keywords: Decision-Making, Robotic System, Voice-Emotions Commands, Voice Recognition, Exceptional Circumstances, Emergency Intervention, Distributed Computing, Human-Machine Interface.